Teknik Pemeriksaan Shoulder Joint dengan Klinis Trauma di RS PKU Muhammadiyah Karanganyar - Ririn Tri Suharti; Ildsa Maulidya Mar’atus Nasokha; Fisnandya Meita Astari (Pusat Riset dan Inovasi Nasional, 2025)
This study aims to examine the technique of Shoulder Joint radiographic examination in trauma cases carried out at PKU Muhammadiyah Hospital Karanganyar. The method used is qualitative descriptive with a case study approach through direct observation, interviews with radiographers, and documentation of examination procedures. The results showed that the radiographic examination was carried out using Posterior Antero Thorax (AP) projection without special preparation, except for the removal of metal objects around the examination area. This projection was chosen because it was able to assess the condition of the shoulder and thorax simultaneously, allowing comparisons between the healthy side and the traumatized side, as well as detecting abnormalities in the costae and lungs with minimal radiation exposure. Although the AP projections provide an overview, this study highlights the importance of developing a specific Standard Operating Procedure (SPO) for the examination of the Shoulder Joint in trauma cases to improve diagnostic consistency and accuracy. The study also recommends the use of additional projections such as the Scapula Y view and Transthoracic Lateral as a complement to obtain a more detailed visualization of the structure of the shoulder joint and surrounding tissues. These findings are expected to be a reference in the development of radiography protocols for shoulder trauma in health care facilities, as well as improve the quality of radiology diagnostic services as a whole.